An Overview of the Semi-arid Climate and Environment Research Observatory over the Loess Plateau - 黄建平 张武 左金清 闭建荣 史晋森 王鑫 常倬林 黄忠伟 杨溯 张北斗 王国印 冯广泓 袁九毅 张镭 左洪超 王式功 符淙斌 丑纪范 (Advances in atmospheric sciences, 2008)
Arid and semi-arid areas comprise about 30% of the earth＇s surface. Changes in climate and climate variability will likely have a significant impact on these regions. The Loess Plateau over Northwest China is a special semi-arid land surface and part of a dust aerosol source. To improve understanding and capture the direct evidence of the impact of human activity on the semi-arid climate over the Loess Plateau, the Semi-Arid Climate and Environment Observatory of Lanzhou University （SACOL） was established in 2005. SACOL consists of a large set of instruments and focuses on： （1） monitoring of long term tendencies in semiarid climate changes; （2） monitoring of the aerosol effect on the water cycle; （3） studies of interaction between land surface and the atmosphere; （4） improving the land surface and climate models; and （5） validation of space-borne observations. This paper presents a description of SACOL objectives, measurements, and sampling strategies. Preliminary observation results are also reviewed in this paper.